Penerapan Metode Socratic Questioning dalam Pembelajaran PAI untuk Membentuk Nalar Kritis Siswa: Application of the Socratic Questioning Method in Islamic Education Learning to Develop Students' Critical Thinking - Ahmad Ardani; Muh. Hanif (ITScience (Information Technology and Science), 2025)
Socratic Questioning is a dialogic approach that has the potential to develop students' critical reasoning in Islamic Religious Education (ISE) learning, but its implementation at the junior high school level has rarely been studied in depth. This study aims to analyze the application of Socratic Questioning by Islamic Religious Education (ISE) teachers and its relevance to the development of critical reasoning in ninth-grade students at SMP Ma'arif NU Karanggedang. This study employs a qualitative method with a descriptive approach to describe the learning situation and phenomena as they occur in the field through an in-depth exploration of teachers' strategies in building tiered dialogues, categorized into six types of Socratic questions. Data were obtained through three main techniques: observation, interviews, and documentation. This study also serves to provide an empirical overview of classroom dynamics and the process of developing critical reasoning in the context of moderate Islamic schools. The results show that the application of clarifying questions, arguments, assumptions, other perspectives, implications, and meta-reflection can encourage students to develop analytical and evaluative skills. This is evidenced by their ability to explain concepts, link arguments to arguments, assess legal implications, and consider differing views of scholars. Teachers play an active role as dialogue facilitators, while a conducive learning environment also strengthens student engagement. The conclusion of this study suggests that Socratic Questioning is effective in developing students' critical reasoning and is relevant for enhancing Islamic Religious Education (PAI) learning through reflective dialogue. This approach opens up opportunities for teacher professional development through training in formulating critical questions and integrating directed dialogue into PAI learning.